Makna Lirik Lagu “Durasi” oleh Feby Putri dalam Kajian Semiotika Roland Barthes - Nirfanda Pratiwi; Nina Queena Hadi Putri (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This research uses qualitative research methods with Roland Barthes Semiotics theory with data on the lyrics of the song “Duration” by Feby Putri which dissects signs in two levels: denotation and connotation, as well as the myths contained in the song text. The main data source in this research is the lyrics of the song “Duration” which is accessed by YouTube on the official Feby Putri NC account, while secondary data is obtained from the website article www.RRI.co.id, music reviews and a podcast entitled “Feby Putri surgical song Duration with Indra Aziz |Dalem banget” on the youtube account VokalPlus by Indra Aziz. The data collection technique was done through documentation. The results showed that denotatively, the lyrics of this song describe the feelings of someone who realizes that being together with the person he loves has a time limit, whether due to circumstances, fate, or changing feelings. Connotatively, this song represents Feby's life story as an overseas child feeling lonely overseas when he returned to his hometown he found significant changes in his family, especially his mother who was getting older. Meanwhile, at the mythical level, this song reflects Indonesian cultural values about the importance of returning to one's hometown because family and loved ones are something very valuable, moments together must be utilized as well as possible because time keeps running and will never be repeated. Thus, the lyrics of Durasi are not just a melancholic song, but also a symbol of universal life reflections that are relevant to many individuals.